Expressões contemporâneas do mal-estar na universidade: temporalidade e escritas da experiência - Guerra, Gabriela Oliveira (2020)
The present research starts from concerns regarding psychological suffering in the university context, produced from the researcher's listening experience as a psychologist in institutions of the federal education network. In this sense, its general objective is to build, from the listening-flânerie, spaces-time for reflection on contemporary expressions of uneasiness in the university. In its specificity, it aims to problematize the suffering socio-political dimension, its expressions and forms of recognition in the university territory; as well as reflecting on the social phenomena of our time, the subjectivation processes and the inscription strategies in the social bond in contemporary times. In addition, it seeks to support, from its productions, the creation of clinical-political intervention devices that enable the passage from living to experience. The methodological approach is defined by research in psychoanalysis. The design of this method is based on the ethical-methodological proposal made by Gurski (2008; 2012; 2014; 2019), in which the referential and psychoanalytical listening are articulated with the constructions of Benjamin's writings on the theme of the experience and flanêur's position in Baudelaire. The research participants - technicians, teachers and students linked to the activities and projects in Clinical and Educational School Psychology at the university - built experience writings. Also included in this study were some discursive fragments of media expressions in current news reports on internet news sites, collected as remnants of social discourse on the topic. The research crossing was traced in the search to frame experience territories, in the transitions for its different spaces and times. The first territory locates the conceptual operators that support the writing construction. The second deals with the ethical-methodological path of research in psychoanalysis and writing as a threshold experience. Finally, the third, which is constructed by the experience narratives in the form of an essay. The problematization regarding the effects of the discourses that organize the social bond in university experiences found tension on our ways of being and living, ways of production and circulation of affections. Coming from the experience that flows from diverse narratives, signifiers that constitute ways to name the uneasiness, to register what is restless, what produces suffering, on the writing thresholds. Helplessness, speed, stagnation, survival, exhaustion, indifference, silence. The importance of this study is present in the spaces and times of reflection forged and in the intention of articulating the research production with the demands in the contemporary social bond, as well as by the support that will give the construction of intervention proposals that value the shared experience.